Communication Between Health Workers and Ethnic Minorities in Vietnam - Shannon McKinn; Duong Thuy Linh; Kirsty Foster; Kirsten McCaffery (SLACK Incorporated, 2017)
Background: Vietnam has made notable progress in reducing maternal mortality rates during the past 2 decades, but this overall improvement conceals regional and ethnic inequalities. Ethnic minorities in Vietnam experience high rates of poverty and mortality, and they face communication and cultural barriers when accessing health services. Poor communication with health professionals combined with limited health literacy is concerning, particularly in the maternal health context, and may exacerbate existing inequalities. Objective: This study explores primary health care professionals' perceptions of the quality of their communication with ethnic minority women during and after pregnancy. Methods: Semi-structured interviews were conducted with 22 primary health care professionals in Dien Bien province. A thematic analysis was performed using a framework analysis method. Key Results: Health professionals had mostly positive perceptions about their communication with ethnic minority women. However, they generally perceived the effectiveness of their communication as being based on women's individual capacities to understand health information (both the language used and the content) and factors such as ethnic and cultural differences, rather than reflecting on the suitability of information and materials or on their own communication skills. This placed much of the burden of communication and understanding health information on ethnic minority women and their families. Conclusions: Health professionals perceived of communication as being mainly a one-way street for the provision of health information, and rarely acknowledged the interactive nature of communication. Patient-professional communication and health literacy in Dien Bien province may be improved through the introduction of patient-centered communication skills training that applies health literacy approaches at the health professional level.